Characterization of QuantiFERON-TB-Plus results in latent tuberculosis infected patients with or without immune-mediated inflammatory diseases. Issue 1 (July 2019) - Chiacchio, Teresa; Petruccioli, Elisa; Vanini, Valentina; Cuzzi, Gilda; Massafra, Umberto; Baldi, Gianpiero; Navarra, Assunta; Scrivo, Rossana; Mastroianni, Claudio; Sauzullo, Ilaria; Esposito, Carmela; Palmieri, Fabrizio; et al.
Highlights: IFN-γ response to QFT-P is lower in IMID-LTBI compared to LTBI without IMID. IMID status does not impact the ability to respond simultaneously to TB1 and TB2. Similar proportion of discordant TB1 and TB2 results in IMID-LTBI and LTBI. IMID-LTBI patients have a high probability to have QFT-P results in the grey zone range. Type of IMID therapy does not impact the distribution of IFNγ results to QFT-P. Summary: Objectives: Screening for latent tuberculosis infection (LTBI) diagnosis is mandatory in patients with immune-mediated inflammatory diseases (IMID) requiring biologics. QuantiFERON-TB-Plus (QFT-P), an LTBI diagnostic test, measures IFN-γ after M. tuberculosis -stimulation in TB1 and TB2 tubes in which a "CD4" or a "CD4 and CD8" response is respectively elicited. Aim of this study is to compare the response to QFT-P of IMID-LTBI patients candidates to a new biological therapy vs LTBI-subjects without IMID. Methods: We prospectively enrolled 167 subjects: 61 IMID-LTBI and 106 NON-IMID-LTBI. Results: All subjects were mitogen-responders. IFN-γ production was significantly lower in IMID-LTBI-patients compared to NON-IMID-LTBI-subjects. We observed discordant TB1 and TB2 results in 6.5% of IMID-LTBI-patients and in 8% of NON-IMID-LTBI-subjects. Applying a logistic regression analysis, we found that IMID-LTBI patients had a higher probability (TB1 stimulation OR 3.32; TB2 stimulation OR 4.33) to have IFNγ results ≤0.7 IU/mL compared to NON-IMID-LTBI-subjects. Interestingly, IMID-treatment did not interfere with the distribution of IFNγ-values. Conclusions: These results indicate that IMID-LTBI-patients have a low IFN-γ response to QFT-P, a high proportion of results ranging in the grey zone and a distribution of IFNγ-values independent from the IMID-treatment. These results are important for the management of LTBI screening in IMID patients.